"Doctor, What Happens After My Anterior Cruciate Ligament Reconstruction?". (20th February 2019) - Houck, Darby A.; Kraeutler, Matthew J.; McCarty, Eric C.; Frank, Rachel M.; Bravman, Jonathan T.
Abstract : It is important to educate patients on what to expect following anterior cruciate ligament (ACL) reconstruction (ACLR), with respect to both the short-term and long-term outcome. A high preinjury activity level, younger age, male sex, positive psychological response to return to sport training, and use of autograft can positively influence a patient's ability to return to sport. There is an increased risk of graft rupture and injury of the contralateral ACL in young active patients, particularly in young female soccer players; nonanatomic tunnel placement and use of (irradiated) allograft tissue also increase the risk of revision. The current literature does not support a prophylactic benefit of ACLR in reducing the rate of knee osteoarthritis after an ACL injury. Meniscal integrity plays an important role in the long-term functional outcome of a patient after ACLR. An ACL injury increases a patient's risk for undergoing a total knee arthroplasty later in life.